Pengaruh Islamic Market Orientation Dan Inovasi Produk Terhadap Kinerja Pemasaran - Nurudin Nurudin; zuhdan ady fataron; Laily Nur Asyifa (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this study was to determine the effect of Islamic market orientation and product innovation on marketing performance. The sample used was 100 people who were collected by non-probability sampling method in the form of purposive sampling. Data collected by distributing questionnaires directly and using a Likert scale. The data analysis technique used is multiple regression analysis. The results of the analysis show that Islamic market orientation has a positive and significant effect on marketing performance. Product innovation has a positive and significant effect on marketing performance.